El confinamiento por el teletrabajo ocasionado por el COVID-19 y la violencia intrafamiliar en el cantón Guaranda. - López Llumiguano, Tobías Fernando (2025)
When discussing violence, we are addressing a term that encompasses a broad range of meanings, considering that violence exists from within the home to both inside and outside a nation. Violence is an issue that has gained increasing prominence over time. This does not mean that violence has never existed; rather, due to changes within society, both in terms of health and economics, violence has become more ingrained within the family unit. A clear example of this occurred during the COVID-19 pandemic, and its repercussions are still evident today. During that period, one of the most significant increases in domestic violence was observed, as the lockdown prevented people from leaving their homes and prohibited all in-person activities. This led to a greater reliance on electronic platforms for both education and work, which contributed to new dynamics in which violence manifested in various ways. As a result of the lockdown and the disease itself, people began to experience stress due to confinement and, of course, the pandemic, which led to conflicts within households as they had to adapt to a new way of life— including in their daily routines, such as telecommuting. Many people no longer maintained physical contact with their families, whether due to work-related issues or other activities. This situation contributed to the onset of abuse and domestic violence in many homes, leading in some cases to fatalities. It is important to note that, given the circumstances, it was somewhat difficult to report these crimes.